Data-driven leadership - Datnow, Amanda; Park, Vicki (San Francisco, CA : Jossey-Bass, 2014)
'School leaders must know how to analyze, interpret, and use data so that they can make informed decisions in all areas of education, ranging from professional development to student learning. This book offers strategies and tools to help launch or fine-tune efforts to become a performance-driven school. Based on the authors' extensive work with 12 schools, the book includes an examination of such essential topics as: establishing a data culture, investing in an information management system, selecting the right data, and analyzing and acting on data to improve performance'--
Includes index.
Keywords: Educational leadership; School improvement programs -- Data processing